Psychological and psychosomatic aspects of the caesarean section experience - Plotti, G.; Pieroni, A. (Medicina e Morale, 1986)
Caesarean section is the only obstetric operation that, by avoiding the vaginal route, allows the fetus to be quickly extracted via the abdominal route. Its performance is therefore justified when there is an indication for rapid delivery or when the vaginal route is contraindicated because the necessary conditions are not met.